Accountability of Women in Faith During the Prophet’s Era - Ahmad, Sajjad; Aslam, Tahir (Journal of Islamic and Religious Studies, 2021)
Allah has sent Prophets in all ages to bring humanity on the right path, self-purification, and enlightenment with the teachings of Allah. Allah has bestowed this ummah through the Prophet (PBUH), a clear and comprehensive guide to worship. He taught the people about the rules and teachings of Allah through revelation which is a complete code of conduct for human beings in beliefs, worships, affairs, society, economy, and morals. Prophet (PBUH) acquainted men and women of their rights and responsibilities. Though He held women accountable in the various aspects, but the first of these was the accuracy of belief and faith. Therefore, we discover many instances of women's accountability in the hadiths, based on which we can reform faith of contemporary women. It is the need of time to reform contemporary women about the correctness of faith. Hence, this article includes the meaning, objectives, types and procedures of accountability in Islam and steps taken by the Holy Prophet in this regard.